Resitusi Tanah yang Dikuasai Negara untuk Kepentingan Proyek Kawasan Inti Pusat Pemerintah Ibu Kota Nusantara dalam Perseptif Hak Asasi Manusia - Arief Kurniawan; Siti Saniah; Ongky Almus (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
The development of the Central Government Core Area (KIPP) of the Capital City of Nusantara (IKN) is a national strategic project that has significant implications, particularly in relation to state control/domination of land. The relocation of the national capital to the Capital City of Nusantara (IKN) has become a strategic agenda of the Indonesian government, which aims to realize equitable development and a new administrative center in Indonesia (Law Number 3 of 2022 concerning the National Capital) and has an impact on all aspects of the lives of indigenous peoples in the IKN Nusantara region, particularly in the field of land. However, this project raises serious issues related to state control of land, especially in terms of the rights of the surrounding communities whose land is affected by the Development of the Central Government Area of the Capital City of Nusantara (KIPP IKN). Land restitution is a central issue because it concerns the guarantee of human rights, particularly the right to ownership, access to land, and social justice (Satjipto Rahardjo, Hukum dan Masyarakat [Law and Society] (Bandung: Alumni, 2000). This study analyzes how land restitution in the KIPP IKN development project is viewed from a human rights perspective, emphasizing the need for a balance between national development interests and the protection of citizens' rights.